Effects of Passive Range Of Motion (ROM) Exercise On Increases Muscle Strength in Non-Hemorrhagic Stroke Patients in the Inpatient Room at RSUD Kota Tangerang - Endah Sri Rahayu; Nuraini Nuraini (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2020)
Stroke is one of the serious health problems in modern life today. According to the World Health Organization (WHO) explained that stroke is the leading cause of death globally. An estimated 17.7 million people die of strokes in 2015 representing 31% of all global deaths. This study aims to determine the effect of Passive Range of Motion (ROM) Exercise on Increasing Muscle Strength in Non-Hemorrhagic Stroke Patients in the Inpatient Room at Rsud Kota Tangerang. Quasi-experimental research design with a sample of 14 people. Univariate and bivariate data analysis using the Wilcoxon test. Samples are measured using Observation Sheets before and after Range Of Motion (ROM) Exercises. This Range Of Motion exercise is carried out for 1 week in 7 days, done 2 times in the morning and afternoon for 15 minutes. Based on the Paired Test, it was found that there was an effect of Passive Range Of Motion (ROM) Exercise on increasing muscle strength in non-hemorrhagic stroke patients with p-value = 0,01 <α 0,05. This proves that passive ROM has an effect on increasing the muscle strength of the respondent. Hospitals should set standard operating procedures for special handling using Passive ROM so that the results obtained can be maximal and uniform for all the problems of the word muscle strength.Keywords: Non-hemorrhagic; stroke; Passive ROM; Muscle Strength